A survey on the application of Carnoy's solution in China - Qi-Wen Man (Elsevier, 2023)
We conducted a survey for the application of Carnoy's solution in oral surgeons of China. The results showed that few oral surgeons use Carnoy's solution for the treatment of the odontogenic keratocyst and the reason for not using Carnoy's solution was the accession difficulty. It should be aware that Carnoy's solution is an effective complementary therapy for treating odontogenic keratocyst but omitted by most oral surgeons.